2013
DOI: 10.1504/ijbhr.2013.054516
|View full text |Cite
|
Sign up to set email alerts
|

The fallacy of one-dimensional theory of planned behaviour structure in predicting health behaviour

Abstract: Most research on exercise is dominated in the West. Drawing on a socio-cognitive theory, this research aims at addressing methodological issues in an Eastern culture where recent developments of the theory of planned behaviour (TPB) applications have been limited. To answer the call for reinterpretation of the TPB measurement, we propose and test a more complex factor structure of TPB predictors. Cross-sectional data was collected from a quota sample of 512 adults in Malaysia. This study provides an empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…And it did not have a significantly different effect between Spanish and Portuguese students. The PBC has shown a volatility in the empirical results related to its influence on the intention and also to a certain lack of agreement regarding the concept and operationalization (Yap et al, 2013). It is a concept that is associated with high self-efficacy and effectiveness (Zhao et al, 2010).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…And it did not have a significantly different effect between Spanish and Portuguese students. The PBC has shown a volatility in the empirical results related to its influence on the intention and also to a certain lack of agreement regarding the concept and operationalization (Yap et al, 2013). It is a concept that is associated with high self-efficacy and effectiveness (Zhao et al, 2010).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Moreover, our results showed that entrepreneurial intention is best represented by three factors-choice intention, commitment to entrepreneurship, and nascent entrepreneurship. A few studies have so far investigated the factorial validity of the complete "two-component" TPB model, and even fewer have attempted to compare the predictive ability of these components on intention (e.g., Courneya et al, 2006;Huang & Chen, 2015;Yap et al, 2013). The results of these studies, which were mostly concentrated on predicting health and exercise behavior, indicate that the complete two-component TPB model fits the data better than the traditional TPB model does (Huang & Chen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PBC is considered as the most controversial construct in the TPB in part because of the inconsistency in the empirical findings related to its influence on intention and in part because of the disagreement regarding its conceptualization and operationalization (Yap, Othman, & Wee, 2013). The PBC concept, when introduced by Ajzen (1991) as another antecedent factor that can predict intention, was defined as a "person's perception of the ease or difficulty of performing the behavior of interest" (Ajzen, 1991, p. 183).…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%
“…The findings revealed that perceived behavioral control predicts significantly stronger than subjective norms on entrepreneurial intentions in both genders, and it did not have an effect significantly different between males and females. Perceived behavioral control is considered as the most controversial construct in the Theory of Planned Behavior for two reasons: the inconsistency in the empirical findings related to its influence on intention and in the disagreement regarding its conceptualization and operationalization ( Yap et al, 2013 ), and it is often associated with self-efficacy ( Zhao et al, 2010 ). Although the difference in the mean between both genders is statistically significant, the values are not high.…”
Section: Discussionmentioning
confidence: 99%